The Impact of Using Online Counseling Platforms and Virtual Community Support on Managing Work Stress among Young Professionals in Jakarta - Herda Ariyani; Emdat Suprayitno; Rival Pahrijal (West Science Social and Humanities Studies, 2024)
This study investigates the effects of online counseling platforms and virtual community support on work-related stress management among young professionals in Jakarta. A quantitative methodology was employed, gathering data from 150 participants via a Likert scale (1-5), and analyzed with SPSS version 26. The findings indicated substantial beneficial correlations between online counseling platforms and virtual community support regarding job stress management. Multiple regression analysis indicated that virtual community support exerted a somewhat greater impact on stress management than online counseling platforms. Collectively, these interventions accounted for 49% of the variance in stress management, suggesting their efficacy in mitigating work-related stress. The findings indicate that combining professional therapy with peer support provides a holistic strategy for the mental well-being of young professionals in urban settings.